Restrukturisasi Budaya Hukum Kejaksaan Dalam Penuntutan Sebagai Independensi di Sistem Peradilan Pidana Indonesia - Appludnopsanji Appludnopsanji; Pujiyono Pujiyono (SASI, 2020)
The position of the prosecutor's office which is under two powers namely executive and judiciary causes the prosecutor's office to become an institution that is not independent and free, thus causing blemishes to commit fraud by prosecutors. This study aims to find out how the reality of the independence of prosecutors in prosecution and know how the cultural rearrangement for prosecutors in prosecution as a process of the criminal justice system. Research methods The research method uses normative research through a conceptual approach and a statue approach. The results showed that the ambiguous position of the prosecutor made the prosecutor hesitant in carrying out their duties, was not independent and was not free and there was a judicial mafia. With regard to this condition, re-structuring of the prosecutor's independence in prosecution is needed. This is intended so that the prosecutor's office becomes an independent institution by integrally restructuring the legal culture together with other criminal justice sub-systems through a religious approach, contextual approach and comparative approach